Pelatihan Penggunaan Theodolite dalam Survei Pemetaan Lahan Pertanian untuk Siswa SMKN 1 Kelayang - Trisnawati, Lisa; Hartika, Dewi; Neswita, Nedra; Sahriyal, Sahriyal; Julinaldi, Julinaldi; Erny, Erny (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Theodolite training for students at SMKN 1 Kelayang aims to boost their understanding and practical skills in agricultural land mapping surveys. The program kicked off by identifying the school's needs for facilities and infrastructure, especially practical equipment, which directly impacts students' knowledge of land surveying. The training was split into classroom theory and field practice. Theory sessions covered theodolite basics, fundamental mapping survey principles, key components, and functions. Pre-test and post-test results showed a significant jump in student knowledge, from 46.67% to 85.70%. Field practice focused on theodolite operations, including setup, measurement, and data processing. Even though students initially struggled, instructor guidance helped them master these skills. This training does more than just equip students with technical expertise in agriculture and mapping; it also cultivates critical thinking and an awareness of accurate data's importance in managing agricultural land resources, ultimately preparing them to compete in the workforce.